Interleukin 2 and interferon alpha-2a do not improve anti-tumour activity of 5-fluorouracil in advanced colorectal cancer. - Goey, S. H. (Nature Publishing Group, 1996)
Treatment using a combination of 5-fluorouracil (5-FU), interferon-alpha (IFN alpha-2a) and interleukin 2 (IL-2) has been shown to mediate disease regression in selected patients with advanced colorectal cancer. This phase II study was designed to evaluate the anti-tumour activity and toxicity of the combination of IL-2, IFN alpha-2a and 5-FU in patients with advanced colorectal cancer. Forty-four patients with metastatic colorectal cancer were treated, predominantly on an outpatient basis, with subcutaneous IFN alpha-2a and IL-2 three times per week followed by once a week bolus intravenous 5-FU injections. There were six (14%) partial responses among the 43 evaluable patients [95% confidence interval (CI) 5-28%]. Twenty-four patients had stable disease (56%) and 13 patients (30%) showed progressive disease. The median time to progressive disease in 43 patients was 19 weeks (range 2-72 weeks) and in responders 34 weeks (range 24-30 weeks). The median overall survival was 47 weeks (range 2-85 weeks) and in responders 60 weeks (range 35-71 weeks). Treatment-related toxic effects included fatigue, nausea and vomiting. Granulocytopenia was the main reason for the dose reductions or treatment interruptions in 32 out of 44 patients. One patient died of toxicity due to renal failure. Serial assessments of immunophenotyping and cytolytic activities of peripheral blood lymphocytes did not show changes in the numbers of circulating natural killer (NK) cells or in the levels of NK and lymphokine-activated killer (LAK) cytolytic activities. This regimen of IL-2 and IFN alpha-2a with 5-FU has only modest anti-tumour activity in advanced colorectal cancer.